PENGARUH BI-RATE DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Zulfaida Nor Aini; Meilany Pramesti Habiba; M. Faizal Rizki; Agus Eko Sujianto (Ekonis: Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of the BI-Rate and inflation on Indonesia’s economic growth during the 2015–2023 period using a quantitative approach through multiple linear regression based on time-series data from Bank Indonesia and the Central Bureau of Statistics. The F-test results show that the BI-Rate and inflation simultaneously have no significant effect on economic growth (Sig = 0.184). Partially, the BI-Rate (Sig = 0.317) and inflation (Sig = 0.412) also demonstrate no significant influence, indicating that changes in the benchmark interest rate and inflation levels during the observed period did not directly determine fluctuations in GDP growth. The coefficient of determination (R² = 0.319) reveals that only 31.9% of the variation in economic growth is explained by the two variables, while the remainder is driven by other factors such as household consumption, investment, fiscal policy, and global economic conditions. These findings suggest that inflation stability and interest rate adjustments were not dominant drivers of Indonesia’s economic performance during the period, highlighting the need for stronger macroeconomic policy coordination, particularly between monetary and fiscal frameworks, to reinforce resilience and support sustainable economic growth.Keywords—BI-Rate, inflation, economic growth, monetary policy, linear regression.